Audit Sistem Informasi Instalasi Rawat Jalan Berdasarkan Perspektif Pelanggan Balanced Scorecard Dan Standar Cobit 4.1 (Studi Kasus: Rumah Sakit Umum Haji Surabaya) - Revinggar, Bilqish Nadia; Tanuwijaya, Haryanto; Mastan, Ignatius Adrian (Jurnal JSIKA, 2012)
Installation Management Information Systems unit in Haji General Hospital (RSU Haji Surabaya) to handling of the processes that one of them is the installation of outpatient information system. This system handles a public patient and cooperation with third parties. Activity in the process include patient registration processes, patient service action, use of health / medicine, history of patient examination, details of the cost of patient care. In managing the process, use some application modules that implement the concept of Enterprise Resource Planning (ERP), where the implementation of the application is primarily an outpatient installations have not been audited to ensure IT alignment with business goals. To measure how far the alignment between business processes, applications, and the company´s business strategy is necessary to do an audit information system with standard CobiT 4.1. Because the calculation of COBIT there that can represent the maturity level of a company. While service quality has a great influence for the installation of outpatient care, the audit focused on the customer perspective of the Balanced Scorecard. The result of this audit stated that the installation process maturity level is at its outpatient-defining process which signifies that the organization has a formal and written standard procedure, but there was no supervision to perform the procedure, allowing the occurrence of many irregularities .. Key words: outpatient installation, CobiT, maturity level, the Balanced Scorecard.